Human aspects of information security and assurance : 14th IFIP WG 11.12 International Symposium, HAISA 2020, Mytilene, Lesbos, Greece, July 8-10, 2020, Proceedings /: 14th IFIP WG 11.12 International Symposium, HAISA 2020, Mytilene, Lesbos, Greece, July 8-10, 2020, Proceedings. ([2020]) - Unknown
No abstract available